Phenomenology of human understanding - Cronin, Brian (Lutterworth Press, 2018)
The problem of human knowing has been foundational for the enterprise of philosophy since the time of Descartes. The great philosophers have offered different accounts of the power and limits of human knowing, but no generally acceptable system has emerged. Contemporary writers have almost given up on this most intractable issue. In 'Phenomenology of Human Understanding', Brian Cronin suggests using the method of introspective description to identify the characteristics of the act of human understanding and knowing. Introspection, far from being private and unverifiable, can be public, communal, and verifiable. If we can describe our dreams and our feelings, then, we can describe our acts of understanding. Using concrete examples, one can identify the activities involved: namely, questioning, researching, getting an idea, expressing a concept, reflecting on the evidence and inferring a conclusion. Each of these activities can be described clearly and in great detail. If we perform these activities well, we can understand and know both truth and value. This book invites readers to verify each and every statement in their own experience of understanding. This is a detailed account of human knowing, an extremely valuable contribution to philosophy and a solution to the foundational problem of knowing.